Chromosome-scale assembly of barley cv. 'Haruna Nijo' as a resource for barley genetics. (12th January 2022) - Sakkour, Areej; Mascher, Martin; Himmelbach, Axel; Haberer, Georg; Lux, Thomas; Spannagl, Manuel; Stein, Nils; Kawamoto, Shoko; Sato, Kazuhiro
Abstract: Cultivated barley ( Hordeum vulgare ssp. vulgare ) is used for food, animal feed, and alcoholic beverages and is widely grown in temperate regions. Both barley and its wild progenitor ( H. vulgare ssp. spontaneum ) have large 5.1-Gb genomes. High-quality chromosome-scale assemblies for several representative barley genotypes, both wild and domesticated, have been constructed recently to populate the nascent barley pan-genome infrastructure. Here, we release a chromosome-scale assembly of the Japanese elite malting barley cultivar 'Haruna Nijo' using a similar methodology as in the barley pan-genome project. The 4.28-Gb assembly had a scaffold N50 size of 18.9 Mb. The assembly showed high collinearity with the barley reference genome 'Morex' cultivar, with some inversions. The pseudomolecule assembly was characterized using transcript evidence of gene projection derived from the reference genome and de novo gene annotation achieved using published full-length cDNA sequences and RNA-Seq data for 'Haruna Nijo'. We found good concordance between our whole-genome assembly and the publicly available BAC clone sequence of 'Haruna Nijo'. Interesting phenotypes have since been identified in Haruna Nijo; its genome sequence assembly will facilitate the identification of the underlying genes.